Tolerating the Unwelcome Guest; How the Host Withstands Persistent Mycobacterium tuberculosis - Olive, Andrew J.; Sassetti, Christopher M. (Frontiers in Immunology, 2018)
Our understanding of the host response to infections has historically focused on “resistance” mechanisms that directly control pathogen replication. However, both pathogen effectors and antimicrobial immune pathways have the capacity to damage host tissue, and the ability to tolerate these insults can also be critical for host survival. These “tolerance” mechanisms may be equally as important as resistance to prevent disease in the context of a persistent infection, such as tuberculosis, when resistance mechanisms are ineffective and the pathogen persists in the tissue for long periods. Host tolerance encompasses a wide range of strategies, many of which involve regulation of the inflammatory response. Here we will examine general strategies used by macrophages and T cells to promote tolerance in the context of tuberculosis, and focus on pathways, such as regulation of inflammasome activation, that are emerging as common mediators of tolerance.